CAUSATIVITY AS THE MAIN CHARACTERISTIC OF RUSSIAN VERBS - Distanova, Gulnara; Abbasova, Aida; Gvozdeva, Elena (Revista Inclusiones, 2021)
In modern Russian, causality is the most important characteristic of verbs. Causativity, effectiveness, logical connection between cause and action, dependence of the result on the nature of the effect are integral to typological description of the corresponding language structures, to definition of causal semantics of causative constructions. Causation is broadly defined as an effect of the subject on the object for the purpose of transforming the reality. Cause-effect relationship follows from this action. In constructions with causative verbs, these verbs have a generalized meaning of influence, change, transformation. In syntagmatics, they realize their valency, among which the presence of the object of action is in evidence.